Impact of Technical Progress on the relationship between Competition and Investment - François Jeanjean (International Telecommunications Society (ITS), 2018)
This paper investigates the impact of technical progress on the relationship between competition an investment. Using a model of oligopoly competition with dierentiated products where firms invest to reduce their marginal cost of production, I find that technical progress, which increases the impact of investment on cost reduction, decreases the level of competition that maximizes investment of the industry. This feature holds also for consumer surplus and Welfare. In the model, competition is measured either by the number of competitors or by the degree of substitutability between oers. Result holds for both measures.Two parametric examples illustrate these features.
Keywords: D21; D43; D92; L13; O31; 330; Market structure; Investment; technical progress; competition